2020
DOI: 10.1177/0971355719893500
|View full text |Cite
|
Sign up to set email alerts
|

Contextual Motivations for Undergraduates’ Entrepreneurial Intentions in Emerging Asian Economies

Abstract: The development of theories to explain and predict the phenomena of entrepreneurship is essential to various stakeholders. Recent entrepreneurship literature has suggested that values motivate entrepreneurial intention, and entrepreneurship is contextual. This study examines contextual motivations of business undergraduates’ entrepreneurial intention across selected emerging Asian economies. The research methodology is quantitative. The measurement instrument consists of items from Portrait Values Questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 147 publications
(242 reference statements)
2
9
0
Order By: Relevance
“…This study considers a sample of 236 students attending an entrepreneurship course at a polytechnic institution in Portugal. This study addresses a relevant research gap in the literature since the vast majority of studies published in the field consider a homogeneous sample of students, which does not allow exploring this phenomenon (Hattab, 2014;Looi, 2020;Passaro et al, 2018). It is acknowledged, however, that some studies explore the role of students' prior work experience but not in a fully comprehensive way.…”
Section: Open Accessmentioning
confidence: 99%
“…This study considers a sample of 236 students attending an entrepreneurship course at a polytechnic institution in Portugal. This study addresses a relevant research gap in the literature since the vast majority of studies published in the field consider a homogeneous sample of students, which does not allow exploring this phenomenon (Hattab, 2014;Looi, 2020;Passaro et al, 2018). It is acknowledged, however, that some studies explore the role of students' prior work experience but not in a fully comprehensive way.…”
Section: Open Accessmentioning
confidence: 99%
“…For Malaysian and Indonesian university students, the openness-to-change values have greater influence on their EI. For Chinese university students, achievement values are more important (Looi, 2020 ).…”
Section: Research Hotspots and Frontsmentioning
confidence: 99%
“…Scholars considered EI to an important variable in most studies. The latest literature on entrepreneurship has reported that values motivated EI, and entrepreneurship was contextual (Looi, 2020). However, higher entrepreneurial activity rates were having a positive correlation with economic growth and employment (Acs & Armington, 2004).…”
Section: Entrepreneurship and Economic Growthmentioning
confidence: 99%